Autologous cryo-shocked neutrophils enable targeted therapy of sepsis via broad-spectrum neutralization of pro-inflammatory cytokines and endotoxins - Gao, Qiuxia; Yan, Yan; Zhang, Jie; Li, Xiaoxue; Wang, Jiamei; Feng, Yi; Li, Peiran; Wang, Huanhuan; Zhang, Yunlong; He, Lingjie; Shan, Zhiyan; Li, Bin (Frontiers in Chemistry, 2024)
Background: Sepsis is a life-threatening disease characterized by multiple organ failure due to excessive activation of the inflammatory response and cytokine storm. Despite recent advances in the clinical use of anti-cytokine biologics, sepsis treatment efficacy and improvements in mortality remain unsatisfactory, largely due to the mechanistic complexity of immune regulation and cytokine interactions. Methods: In this study, a broad-spectrum anti-inflammatory and endotoxin neutralization strategy was developed based on autologous “cryo-shocked” neutrophils (CS-Neus) for the management of sepsis. Neutrophils were frozen to death using a novel liquid nitrogen “cryo-shock” strategy. The CS-Neus retained the source cell membrane structure and functions related to inflammatory site targeting, broad-spectrum inflammatory cytokines, and endotoxin (LPS) neutralizing properties. This strategy aimed to disable harmful pro-inflammatory functions of neutrophils, such as cytokine secretion. Autologous cell-based therapy strategies were employed to avoid immune rejection and enhance treatment safety. Results: In both LPS-induced sepsis mouse models and clinical patient-derived blood samples, CS-Neus treatment significantly ameliorated cytokine storms by removing inflammatory cytokines and endotoxin. The therapy showed notable anti-inflammatory therapeutic effects and improved the survival rate of mice. Discussion: The results of this study demonstrate the potential of autologous “cryo-shocked” neutrophils as a promising therapeutic approach for managing sepsis. By targeting inflammatory organs and exhibiting anti-inflammatory activity, CS-Neus offer a novel strategy to combat the complexities of sepsis treatment. Further research and clinical trials are needed to validate the efficacy and safety of this approach in broader populations and settings.